Implementasi Fun Learning Dengan Hour of Code Untuk Meningkatkan Minat Belajar Coding Pada Siswa - Mardhiah Fadhli; Yuli Fitrisia; Dini Nurmalasari; Sugeng Purwantoro; Memen Akbar (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2023)
The importance of studying computer programming for students is that students will gain the ability to think computationally systematically, which includes a more robust way of thinking (robust) in looking at a problem. However, learning computer programming is often considered complicated and requires regular practice. The current condition of the partner, namely SMKN 1 Dumai, is the lack of student interest in learning, curiosity, and the joy of learning coding. This is caused by many factors, one of which is the assumption that students learn coding is something that is complicated and boring. In addition, it is also caused by the learning strategies and methods applied by the teacher are not sufficiently capable of arousing students' curiosity about the lesson. The learning process which is not conducive and the low interest in student learning can be handled by the teacher by providing material in a fun way (fun learning). One way to learn basic coding in a fun way is to learn with hours of code in the game Minecraft. This community service activity was carried out on September 6, 2022, with a total of 22 participants. The results of this activity were in the form of an evaluation of activities through a questionnaire and the result was that 89,90% of the training participants understood the material and were able to practice the Minecraft game project themselves. In addition, the participants were very enthusiastic about participating in the activity because it was presented with fun activities, such as playing games. Based on the results of the questionnaire, training recommendations were also obtained for the next activity in the form of training in implementing the Internet of Things (IoT) project.